Modulación de la expresión génica por vitaminas liposolubles (2006)
ABSTRACT: Most specialized cells of multicellular organisms respond to extra cellular signals affecting gene expression. Nutrients are structural components of the body and vitamins are involved in metabolic process as regulators of the gene expression and their products are cellular components. Many macro and micronutrients modulate cellular transcription. However, fat-soluble vitamins are the most studied nutrients, because of their metabolism on genetic process. The main purpose of this review is to describe the role of fat-soluble vitamins: A, D, E and K on the genetic expression modulation.